Genetic Variability and Characters Associations in Rapeseed (Brassica napus L.) (Bangladesh Journal of Plant Breeding and Genetics, 2016)
Thirty eight rapeseed genotypes were evaluated to estimate the genetic variability and association among the genotypes, following 8 quantitative characters. A considerable amount of genetic variability were found ranges from 1000 seed weight (11.09g) to harvest index (44.00%) and phenotypic variability for plant height (13.36m) to harvest index (44.14%). High heritability was found for all characters except 1000 seed weight (67.04g). Minimum genetic advance was observed for 1000 seed weight (0.63g) and maximum for plant height (29.72m). The lowest genetic advance in percent of mean was found in 1000 seed weight (18.70g) and highest in harvest index (90.35%). Plant height, raceme length and 1000 seed weight have significant positive association with yield with harvest index. Plant height, raceme length, 1000 seed weight and harvest index have imposed direct positive effect on yield per plant (g). As Plant height, raceme length, 1000 seed weight and harvest index are mainly driven by the additive genes so that selection criteria based on this characters should be effective.Bangladesh J. Pl. Breed. Genet., 29(2): 11-16, 2016